PERAN ORANG TUA DALAM IMPLEMENTASI PROGRAM KEAGAMAAN ANAK USIA DINI PADA KB-TK AN-NISA KRIAN SIDOARJO - Asy'ari, Hasyim; Indri M, Dwi Bhakti (Martabat: Jurnal Perempuan dan Anak, 2019)
Parents hold roles in supporting their children in learning. Parents’ involvement in educating their children is essential, especially on the religious matters. In teaching religious knowledge to the early aged children, parents play a huge role in teaching religious basis and internalize as well as habituate Islamic character. In KB-TK An-Nisa, the parents are demanded to be involved in the development of early aged chidren’s religious knowledge and practices. The education organizer of KB-TK An-Nisa prepared the learning activities by socialization to the parents and designing a learning syllabus to be learned by the child. The learning material for early aged children in TK-KB An-Nisa was in the form of the short surahs and hadith memorization, and habituation of ibadah as well as character building. The methods employed by the parents were role modelling, habituation, repetition, memorization, and advice. The forms of monitoring and evaluation on the parent’s involvement in the children learning process were by Whatsapp group message, parents meeting, and the children’s learning report at the end of the semester or at the end of the year. Parents’ involvement brings significant impacts on children's learning result.